Critical Digital Studies : A Reader, Second Edition - Kroker, Marilouise; Kroker, Arthur, 1945- (Book collections on Project MUSE., 2013)
Bringing together the leading scholars in this growing field, internationally renowned scholars Arthur and Marilouise Kroker present an innovative and interdisciplinary survey of the relationship between humanity and technology.